2017
DOI: 10.12973/ejmste/80352
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Impactful Research Experiences for Teachers (RETs)

Abstract: The National Science Foundation (NSF) in the United States funds Research Experiences for Teachers (RETs) for K-12 science teachers. The RET program seeks to provide science teachers with research experiences so they can provide enhanced science or engineering inquiry experiences for their students. One form of RET that focuses on science pedagogy has resulted in some promising changes in teachers' thinking and lesson design. This case study examines how a cohort of ten secondary science teachers' inquiry conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…, 2015; Godin et al. , 2015; Miranda and Damico, 2015; Blanchard and Sampson, 2017; Hardré et al. , 2017; Ragusa and Juarez, 2017); and K–12 assessments (Silverstein et al.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 99%
“…, 2015; Godin et al. , 2015; Miranda and Damico, 2015; Blanchard and Sampson, 2017; Hardré et al. , 2017; Ragusa and Juarez, 2017); and K–12 assessments (Silverstein et al.…”
Section: Discussion Implications and Directions For Future Researchmentioning
confidence: 99%
“…The literature on short-term research experiences such as RETs demonstrates that teachers' participation in the research experiences with scientists can improve their understandings of scientific inquiry (Bahbah et al, 2013;Blanchard & Sampson, 2018;Buxner, 2014;Herrington et al, 2016), perceptions of inquiry (Peters-Burton et al, 2015), confidence in science and inquiry (Cutucache et al, 2017), and views of scientific inquiry (Hughes et al, 2012). However, it has also been demonstrated that the teachers' conceptions of the practices of science remain naïve even after completing an RET (Ozalp, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, mixed results were obtained with regard to the changes in teacher practices (Capps et al, 2012 ; Krim et al, 2019 ; Sadler et al, 2010 ). While difficulties associated with the transfer of the RE to the classroom context were reported by some studies (Brown & Melear, 2007 ; Schwartz et al, 2013 ), others reported changes (Blanchard & Sampson, 2018 ; Hughes et al, 2012 ). Nevertheless, in some of these investigations, direct analysis of teacher practices was not considered, and the assessment is based on self-reported data through interviews or based on information sent by the participants (videos or lessons plans).…”
Section: Introductionmentioning
confidence: 98%